On passion and sports fans: A look at football - Vallerand, R. J.; Ntoumanis, N.; Philippe, F. L.; Lavigne, G. L.; Carbonneau, N.; Bonneville, A.; Lagace-Labont, C.; Maliha, G. (Journal of Sports Sciences, 2008)
The purpose of the present research was to test the applicability of the Dualistic Model of Passion (Vallerand et al., 2003) to being a sport (football) fan. Three studies provided support for this dualistic conceptualization of passion. Study 1 showed that harmonious passion was positively associated with adaptive behaviours (e.g. celebrate the team's victory), whereas obsessive passion was positively associated with maladaptive behaviours (e.g. risking losing one's job to go to a game). Study 2 used a short Passion Scale and showed that harmonious passion was positively related to the positive affective life of fans during the 2006 FIFA World Cup, psychological health (self-esteem and life satisfaction), and public displays of adaptive behaviours (e.g. celebrate the team's victory into the streets), whereas obsessive passion was predictive of maladaptive affective life (e.g. hating opposing teams' fans) and behaviours (e.g. mocking opposing teams' fans). Finally, Study 3 examined the role of obsessive passion as a predictor of partner's conflict that in turn undermined partner's relationship satisfaction. Overall, the present results provided support for the Dualistic Model of Passion. The conceptual and applied implications of the findings are discussed.